Consanguinity and complex cardiac anomalies with situs ambiguus. Issue 3 (March 1984) - Gatrad, A R; Read, A P; Watson, G H
Abstract : A survey of British born Asian and English populations of children with congenital cardiac anomalies showed an increased incidence in the Muslim Asian population of complex lesions with visceral heterotaxia. There is a very high incidence of parental consanguinity among Muslim Asian children with complex congenital cardiac anomalies that is even higher than in the general Muslim Asian population of the area studied. The evidence suggests an important recessive genetic component in complex cardiac lesions with visceral heterotaxia, but segregation analysis does not support pure recessive inheritance.